COVID-19 job and income loss and mental health: the mediating roles of financial assets and well-being and the moderating role of race/ethnicity. Issue 1 (2nd January 2023) - Despard, Mathieu; Banks, Andrae; Dukes, Lyneisha
ABSTRACT: Prior research shows unemployment has a negative effect on mental health, yet whether this relationship is affected by financial factors is unknown. For example, having money in savings may mitigate the impact of job loss on mental health. We use structural equation modeling with data from the Socio-Economic Impacts of COVID-19 Survey with a nationally representative sample ( N = 3, 341) to examine COVID-19 related job loss and mental health as partially mediated by liquid assets and Financial Well-Being (FWB) and moderated by race and ethnicity as moderators. More than a quarter (28.34%) of participants said they experienced a job or income loss due to COVID-19, which was associated with greater psychological distress as measured by the PHQ-4. The structural model had excellent fit (RMSEA = 0.021); FWB partially mediated the relationship between job/income loss and mental health ( p < .001), accounting for 49% of the total effect. However, liquid financial assets did not partially mediate this relationship. Black participants experienced very different direct and indirect effects. Social workers should assess and intervene concerning financial factors when individuals experience job loss. Job loss is different among Black individuals who face greater challenges related to structural racism yet also have greater resilience.